Executive Committee Minutes 2008-09-25 - Academic Senate:::::::::
Resolution opposing Proposition 8, Voluntary System of Accountability, Senate Discussions on WASC, Remedies response reports and discussion, including report from Ad-Hoc Committee, Four Unit Courses